SOIL AND WATER CONSERVATION TECHNIQUES: EXPLORING SUSTAINABLE PRACTICES FOR ECOSYSTEM RESTORATION AND RESOURCE MANAGEMENT - Dani Lukman Hakim; Shari Lee; Kamil Farado (Yayasan Adra Karima Hubbi, 2026)
Environmental degradation and resource scarcity necessitate an urgent transition toward integrated landscape management. This research addresses the critical challenges of soil erosion and water depletion by evaluating the effectiveness of integrated Soil and Water Conservation (SWC) techniques. The study aims to identify synergistic practices that optimize ecosystem restoration and ensure long-term resource sustainability. Utilizing a longitudinal experimental design over twenty-four months, researchers compared mechanical interventions, such as bench terracing, with biological strategies, including cover cropping and bio-swales, across forty-five stratified sample plots. Results demonstrate that integrated approaches outperform isolated methods, reducing sediment loss by over 80% and increasing water infiltration rates by 270%. Significant gains in soil organic carbon and macrofauna diversity further indicate a rapid recovery of functional ecosystem services. The findings confirm that the interaction between physical stabilization and biological enrichment creates a self-reinforcing cycle of land regeneration. This research concludes that adopting holistic, nature-based infrastructure is essential for climate resilience and global food security. The developed sustainability framework provides a scalable model for policymakers to transition from extractive land use to regenerative management, ensuring the ecological integrity of vital terrestrial resources.